Mathematical connection ability on Knisley Mathematics Learning Model with an open-ended approach based on self regulated learning - Oktafiana, Krisna; Dewi, Nuriana Rachmani (Unnes Journal of Mathematics Education, 2020)
The purpose of this study was to explore the mathematical connection ability of 8th graders in the setting of the Knisley mathematics learning model with an open-ended approach. This type of research is mixed methods while the population is 8th graders in one JHS in Semarang, and the sample is a class selected by random cluster sampling. For the qualitative study, six subjects were selected by purposive sampling technique. Data analysis was performed by analyzing quantitative data and analyzing qualitative data. The results showed that (1) The mathematical connection ability of 8th graders in the Knisley mathematics learning model with open-ended approach achieved classical completeness; (2) the average mathematical connection ability of 8th graders in the Knisley mathematics learning model with an open-ended approach is better than conventional learning model; (3) the proportion of 8th graders who completed the learning subject in the Knisley mathematics learning model with an open ended approach is more than the conventional learning model; and (4) several subjects were able to fulfill all indicators of mathematical connection ability while other subjects were able to master some indicators of mathematical connection ability.